Some aspects of visual functions and serum retinol levels in young adults and middle aged subjects - Aung, Nilar; Ohmar, Ohmar; Wai, Nyunt (2011)
The comparism of the dark adaptation and plasma retinol level (Vitamin A) was a potentially useful method of studying the basic nature of the aging process in vision. The purpose of this study was to determine the effect of age upon the dark adaptation time and plasma retinol level. Dark adaptation time, visual fields and plasma retinol levels were studied in two different age groups of Myanmar subjects (young adults: 18-25 years and middle-aged subjects: 40-60 years) (n=30 each). Dark adaptation time (DAT) was determined by a rapid dark adaptation test adopted from Thornton (1977). Visual field was assessed by manually setting kinetic perimetry. Plasma retinol level was determined by colorimetric method using trifluoroacetic acid (TFA). None of the subjects exhibited subnormal plasma retinol levels. Although the plasma retinol levels of middle-aged subjects were comparable to those of their younger counterparts (66.3 (5.2) µg/dl vs 61.4(8.1) µg/dl) (mean(SD)), the middle-aged subjects had significantly longer DAT (5.7 (1.4) vs 3.6 (1.3) minutes; P<0.05) and significantly greater reduction (P<0.05) in visual fields of both eyes. There was a significant negative correlation (P<0.05) between plasma retinol level and DAT in the middle-aged subjects, but not in young adults. No correlation was found between serum retinol level and visual field reduction in both groups. Even with comparable plasma retinol level, longer DAT and greater reduction of visual field in middle-aged subjects indicated that retinal function might also be affected by the age-related changes in retina. Keywords: Dark Adaptation Time (DAT), Rapid Dark Adaptation Test, Vitamin A, Visual Field, Aging.